Condições socioeconômicas e degradação dos recursos naturais na zona rural de Vitória do Mearim - Fernandes, Rachel Torquato (2005)
This paper proposes to measure the quality patterns Vitória do Mearim municipality of Maranhão State. In addition it tried to evaluate the actual stage of degradation and preservation of natural resources base in this county identifying eventual factors which have contributed for the dynamics of this process for the last 50 years. In order to search targets were selected 14 group of people distributed in all part of this county, just to guarantee to cover its different characteristics concerning to ecosystem, vegetal cover, and landscape. It was randomized selected a sample of 136 farm families living in those group of people and applied a pre-codified formulary. To find out causes and dynamics of degradation over the natural resources of Vitória do Mearim, we selected intentionally 15 persons over 65 years old. The results showed that there is a very low standard of living in the rural areas of Vitória do Mearim county. The majority of the farmers are landless in various categories. The agricultural activities are the principal source of monetary income for rural farms. The field research also showed that there was a very strong pressure over the ecosystem and a complete absence of technical assistance from the public power. It was also observed that the agricultural cultivation is used to feed the families, so people has difficult to produce over this necessity and becomes very difficult to get any kind of monetary income in their production process. The principal crop is cassava which spread over all the investigated families. From cassava, almost all the times, comes the only source of monetary income for the searched families. The itinerant agriculture using cutting the vegetal cover of land and using fire in order to clean the areas is a factor responsible by the pressure over the natural ecosystem. Other cause of this situation is the absence of adequate technologies and the pressure of the increasing of population. All these impacts affect the capacity of land to produce crops productivity as well income and well being of the families. In order to break out the poverty cycle and the to improve the quality of natural resource in this situation it is necessary to search forms of income and employment generation in this county. The public politics must be directed to improve the economic potentiality of Vitória do Mearim, using agriculture, fishery and extrativism, based in epistemology and founded on agro-ecology principles. All these politics must be planned and executed on social bases, and have to be induced by scientific search like this one, environmental education and rural extension.